Competence of Islamic Religious Education Lecturers, Faculty of Islamic Studies, Uisu in Information Technology-Based Learning - Parianto, Parianto; Kalsum, Umi (LPPPIPublishing, 2024)
Along with the passage of time and the increasing level of intellectuality and quality of life, the dimensions of education are increasingly complex, and require appropriate educational design. The role of learning media is very important in the teaching and learning process because it helps students to facilitate understanding of the contents of the material being taught. Based on observations and interviews with PAI FAI UISU lecturers, teachers in utilizing ICT-based learning media are still limited and learning activities are less varied, not interesting and still tend to be conventional. The problem of this study is how is the competence of lecturers in designing, producing and utilizing learning media?, while the purpose of this study is to analyze and describe the competence of lecturers in designing, producing and utilizing learning media. This research is a field survey research. The subjects of this study were nine PAI FAI UISU lecturers. The research method used is quantitative descriptive percentage, while the data collection technique is using a questionnaire. The results of the study obtained were that the competence of lecturers in designing learning media got an average score of 24.7 with a sufficient category, the competence of lecturers in producing learning media got an average score of 22.7 with a sufficient category, and the competence of lecturers in utilizing learning media got an average score of 29.72 with a good category. The conclusion in this study is that the competence of lecturers in designing and producing media is included in the sufficient category, while in utilizing media it is good. The suggestion that can be given is that lecturers should improve their competence in designing, producing and utilizing ICT-based learning media to support the learning process.